2007
DOI: 10.1093/aje/kwm008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Deployment on the Occurrence of Child Maltreatment in Military and Nonmilitary Families

Abstract: War has a profound emotional impact on military personnel and their families, but little is known about how deployment-related stress impacts the occurrence of child maltreatment in military families. This time-series analysis of Texas child maltreatment data from 2000 to 2003 examined changes in the occurrence of child maltreatment in military and nonmilitary families over time and the impact of recent deployment increases. The rate of occurrence of substantiated maltreatment in military families was twice as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(131 citation statements)
references
References 13 publications
5
122
1
3
Order By: Relevance
“…Domestic violence has also generally been shown to be associated with deployment (MacDermid Wadsworth 2010). Rates of substantiated child maltreatment among military families in Texas were higher after October 2002 than they had been prior to this date (Rentz et al 2007); rates increased specifically during periods of deployment and reintegration. Similarly, among families of enlisted soldiers who had one or more substantiated reports of child maltreatment, child maltreatment was higher during periods of deployment ).…”
Section: Current Eramentioning
confidence: 79%
“…Domestic violence has also generally been shown to be associated with deployment (MacDermid Wadsworth 2010). Rates of substantiated child maltreatment among military families in Texas were higher after October 2002 than they had been prior to this date (Rentz et al 2007); rates increased specifically during periods of deployment and reintegration. Similarly, among families of enlisted soldiers who had one or more substantiated reports of child maltreatment, child maltreatment was higher during periods of deployment ).…”
Section: Current Eramentioning
confidence: 79%
“…For nondeployed spouses, Spera (2009) found that military "unit relationship quality, leadership effectiveness, and tangible social support from community members" were the most important protective factors to well-being (p. 286). For returned personnel, Rentz et al (2007) outlined that protective factors such as disciplinary measures particular to the military may help decrease the prevalence of family violence and addictions, but unfortunately these measures may increase the likelihood of nondisclosure due to stigma and fear of curtailed career progression. For children experiencing difficulties during deployment, Saltzman et al (2011) explained that nurturing and adaptive parenting are the most important protective factors.…”
Section: Protective Factors In Military Familiesmentioning
confidence: 99%
“…Recent prolonged deployments in support of the global war on terrorism have been associated with increased risk for child maltreatment. 15,16 Additionally, as many as 30%-60% of military service members have histories of being victims of childhood maltreatment, and some studies have associated such victimization with an increased risk for perpetrating abuse in adulthood. [17][18][19][20] Studies comparing child maltreatment between military and civilian families both support and refute the notion that children in military families are at increased risk for abuse, 16,[21][22][23][24][25][26] but all demonstrate that abuse is an important issue in the military.…”
Section: Discussionmentioning
confidence: 99%